The risk of a subsequent cancer diagnosis after herpes zoster infection: primary care database study. - Cotton, S; Belcher, J; Rose, P; K Jagadeesan, S; Neal, R (2013)
BACKGROUND: Herpes zoster and cancer are associated with immunosuppression. Zoster occurs more often in patients with an established cancer diagnosis. Current evidence suggests some risk of cancer after zoster but is inconclusive. We aimed to assess the risk of cancer following zoster and the impact of prior zoster on cancer survival. METHODS: A primary care database retrospective cohort study was undertaken. Subjects with zoster were matched to patients without zoster. Risk of cancer following zoster was assessed by generating hazard ratios using Cox regression. Time to cancer was generated from the index date of zoster diagnosis. RESULTS: In total, 2054 cancers were identified in 74,029 patients (13,428 zoster, 60,601 matches). The hazard ratio for cancer diagnosis after zoster was 2.42 (95% confidence interval 2.21, 2.66) and the median time to cancer diagnosis was 815 days. Hazard ratios varied between cancers, and were highest in younger patients. There were more cancers in patients with zoster than those without for all age groups and both genders. Prior immunosuppression was not associated with change in risk, and diagnosis of zoster before cancer did not affect survival. CONCLUSION: This study establishes an association between zoster and future diagnosis of cancer having implications for cancer case finding after zoster diagnosis.